2021
DOI: 10.1186/s12931-021-01714-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative outcomes in patients receiving pirfenidone or nintedanib for idiopathic pulmonary fibrosis

Abstract: Background Real-world data regarding outcomes of idiopathic pulmonary fibrosis (IPF) are scarce, outside of registries. In France, pirfenidone and nintedanib are only reimbursed for documented IPF, with similar reimbursement criteria with respect to disease characteristics, prescription through a dedicated form, and IPF diagnosis established in multidisciplinary discussion. Research question The data of the comprehensive French National Health Syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 35 publications
(39 reference statements)
1
18
0
Order By: Relevance
“…In SA2 the treatment discontinuation was rather high, with 50.7% of pirfenidone-treated and 44.0% of nintedanib-treated patients. Similar high discontinuation rates were also reported in other claims data based studies [ 12 , 13 , 34 ]. One possible explanation for the difference in the discontinuation rates between the drugs in our study is that nintedanib was approved during the study period.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…In SA2 the treatment discontinuation was rather high, with 50.7% of pirfenidone-treated and 44.0% of nintedanib-treated patients. Similar high discontinuation rates were also reported in other claims data based studies [ 12 , 13 , 34 ]. One possible explanation for the difference in the discontinuation rates between the drugs in our study is that nintedanib was approved during the study period.…”
Section: Discussionsupporting
confidence: 88%
“…The population included was comparable to ours in terms of space of time, data source (insurance data base), and age of patients. However, a recently published study with data from the French National Health System reported a greater risk of all-cause mortality in nintedanib-treated patients [ 13 ]. The study covered a similar time horizon, sample size, population’s age, and sex distribution as our study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations